Development of Electronic Students’ Worksheet Linear Function-Problem Based Using Desmos Application - Dyah Ayu Karindra Oktaviane; Rooselyna Ekawati (Mathematics Education Study Program, 2022)
One effort to facilitate students in online learning and face-to-face learning during Covid-19 pandemic is the use of digital student worksheets, as an effort to practice students’ cognitive in mathematics. These research goals are to develop digital students’ worksheet of linear function-problem based using Desmos to decrease learning loss effect in students’ motivation and comprehension. And, also to know, the eligibility analysis result of worksheet that has already been made. Desmos is a web-based application, which specially created to be used in mathematics learning. It combines features of graphic calculator and classroom activities to help students study and love math. Research model in this study used ADDIE with a small group experiment using six students of SMPN 3 Surabaya as subjects. Eligibility analysis from the worksheet gains a validity score of 3.71, with very valid criteria. Practical score 3.74, with very practical criteria. And effective, since all six subjects in Study Result Test, gain higher score than the minimum score criteria of SMPN 3 Surabaya. It may take note that, it needs bigger experiments with more subjects to evaluate effective aspect further and comprehensively. This worksheet can be an alternative media for secondary students to practice linear function.